2023
DOI: 10.1101/2023.02.02.526785
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PerTurboID: A targeted in situ method to measure changes in a local protein environment reveals the impact of kinase deletion on cytoadhesion in malaria causing parasites

Abstract: Reverse genetics is key to understanding protein function, but the mechanistic connection between a gene of interest and the observed phenotype is not always clear. Here we describe the use of proximity labeling using TurboID and site-specific quantification of biotinylated peptides to measure changes to the local protein environment of selected targets upon perturbation. We apply this technique, which we call PerTurboID, to understand how the P. falciparum exported kinase, FIKK4.1, regulates the function of t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…One elegant application of proximity labeling has recently been shown in a preprint published by Davies et al [212] The authors used TurboID-based proximity labeling (PerTurboID) and observed that several MC proteins with N-terminal transmembrane domains were inserted into the membrane of the organelle in the opposite direction. [212] The study further assessed the role the kinase FIKK4.1 plays in the function of PfEMP1, which shows the potential of proximity labeling in deciphering PfEMP1. [212] Further, non-genetic approaches are an appropriate way of examining the exportome of P. falciparum and proteins destined for the MC and the RBC surface.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One elegant application of proximity labeling has recently been shown in a preprint published by Davies et al [212] The authors used TurboID-based proximity labeling (PerTurboID) and observed that several MC proteins with N-terminal transmembrane domains were inserted into the membrane of the organelle in the opposite direction. [212] The study further assessed the role the kinase FIKK4.1 plays in the function of PfEMP1, which shows the potential of proximity labeling in deciphering PfEMP1. [212] Further, non-genetic approaches are an appropriate way of examining the exportome of P. falciparum and proteins destined for the MC and the RBC surface.…”
Section: Discussionmentioning
confidence: 99%
“…[212] The study further assessed the role the kinase FIKK4.1 plays in the function of PfEMP1, which shows the potential of proximity labeling in deciphering PfEMP1. [212] Further, non-genetic approaches are an appropriate way of examining the exportome of P. falciparum and proteins destined for the MC and the RBC surface. Ready-to-use small molecular probes (e.g., for click chemistry) from the field of chemical biology permit a fast assessment of proteins at every developmental stage of P. falciparum using different experimental approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation